Vključevanje umetne inteligence pri obravnavi psiholoških vsebin v izobraževanju bodočih učiteljev - Kranjec, Eva (Revija inovativna pedagogika, 2026)
The integration of artificial intelligence (AI) into education requires consideration of ethical principles and maintenance of professional judgment regarding the generated results.The purpose of thisarticle is to present an example of a pedagogical activity in which students, future primary school teachers, used AI in developmental psychological content while developing an understanding of children’s social behavior, critical evaluation of interpretations, and ethical sensitivity. The activity was designed in two stages: analysis of hypothetical cases without AI, followed by analysis of the same cases using generative AI tools. This design enabled a comparison between students’ own interpretations and AI-generated outputs, as well as reflection on their strengths and limitations. The results indicate that students recognize the usefulness of AI forstructuring and illustrating theoretical concepts, while also identifying risks such as overgeneralization, stereotypical interpretations, and erroneous inferences. At the same time, they report lower confidence in their ability to critically evaluate AI-generated content and recognize situations in which responses are less reliable. The article highlights the importance of responsible AI use, clear guidelines, and the systematic development of critical and ethical judgment in the initial education of future teachers.
Keywords: critical judgment; digital competencies of future teachers; digitalne kompetence bodočih učiteljev; ethical use of AI; etična uporaba UI; kritična presoja; students; študenti; Umetna inteligenca; Vzgoja in izobraževanje